(3LhGgQ GdCMcGe heYjf GdbVGI hGdMcGes - (3eMeO Hf eMehO Hf eMeO GdCbMUGQj,J (B961 (3g` s ((3eMeO Hf LYaQ Hf HGdi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi NdbfG Ydi edI GdESdGe CeG HYO aEf CMhL YHGO Gddg Edi QMeJg eMeO Hf eMehO Hf eMeO bGd (B: (3deG EHJdjJ HELQGA GdCMcGe GdTQYjI LeYJ GdcJH GdeJOGhdI ef GdeJhf hGdaJGhi hSejJg HLhGgQ GdCMcGe dchfg egekG ddbVGg hGdMcGe s
(3BNQgG (B:s
(3hPdc eJaGhJ HbdI eGd GdUHi hcKQJg hENJdGa MGdg ajfXQ ai eGdg hMGdg hjfab Ydjg bOQ eG jdjb Hg , hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdMeQIs
(3HChdgG hbajI HGSe YdGeI HjQhJ GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbi s
(3Hg eWGdH ddcJGH s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdESdGejs